2022
DOI: 10.3390/en15103510
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Uncertainties on Crude Oil Prices: Based on a Quantile-on-Quantile Method

Abstract: There has always been a complex relationship between uncertainty and crude oil prices. Three types of uncertainty, i.e., economic policy uncertainty, geopolitical risk uncertainty, and climate policy uncertainty (EPU, GPR, and CPU for short), have exacerbated abnormal fluctuations in the energy market, making crude oil prices volatile more and more frequently, especially from the perspective of the financial attribute of crude oil. Based on the time-series data related to uncertainties and crude oil prices fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…This suggests that when geopolitical risk grows, consumers of crude oil who are extremely sensitive to such risk seek renewable energy as an alternative to traditional energy sources. Ding et al (2022) evaluated the crude oil price's sensitivity to economic policy uncertainty, geopolitical risk and climate policy uncertainty. The study shows that oil prices become riskier and uncertain when energy sector anomalies intensify.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that when geopolitical risk grows, consumers of crude oil who are extremely sensitive to such risk seek renewable energy as an alternative to traditional energy sources. Ding et al (2022) evaluated the crude oil price's sensitivity to economic policy uncertainty, geopolitical risk and climate policy uncertainty. The study shows that oil prices become riskier and uncertain when energy sector anomalies intensify.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As crude oil customers are sensitive to geopolitical risk, they see clean energy as an alternative to traditional energy. Similarly, Ding et al (2022) examine the sensitivity of crude oil prices to economic policy uncertainty, geopolitical risk, and climate policy uncertainty. The study shows that energy sector volatility has increased, making crude oil prices more volatile.…”
Section: Introductionmentioning
confidence: 99%
“…Using partial and multiple wavelet coherence analysis, Choi (2022) found interdependency between GPR and the unpredictability of North-East Asian stock indices. Ding et al . (2022) employ the QQR approach based on the wavelet transform to study the heterogeneous effects of EPU, GPR and climate policy uncertainty at different time scales on crude oil prices.…”
Section: Review Of Literature and Theoretical Frameworkmentioning
confidence: 99%
“…Using partial and multiple wavelet coherence analysis, Choi (2022) found interdependency between GPR and the unpredictability of North-East Asian stock indices. Ding et al (2022) employ the QQR approach based on the wavelet transform to study the heterogeneous effects of EPU, GPR and climate policy uncertainty at different time scales on crude oil prices. Geopolitical concerns and uncertainty in global economic policy have a major long-term impact on variations in the price of oil, according to Wang et al (2022), who employ a bivariate quantile causality nonparametric test and wavelet coherence analysis.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A review of past literature indicated a number of research that explicitly focused on the impact of geopolitical events on palm oil. For example, scholars [ 7 ] claimed that uncertainty and crude oil prices have always had a complex relationship. Three types of uncertainty, i.e., economic policy uncertainty, geopolitical risk uncertainty and climate policy uncertainty, have exacerbated abnormal fluctuations in the energy market, making crude oil prices volatile more and more frequently, especially from the perspective of the financial attribute of crude oil.…”
Section: Introductionmentioning
confidence: 99%